Relationship between Peer-Group Influence and Moral Activities among in School Adolescents in Kwara State - Obiageli, Uyanne Elizabeth; Nasiru, Olokooba Issa (Faculty of Social Science, Universitas Negeri Semarang, 2021)
This study investigated the relationship between peer group influence and moral activities among in-school adolescents in Ilorin South Local Government Area, Kwara State, Nigeria. The objectives of the study were to investigate level of in-school adolescent, types of moral actions displayed and relationship between peer group influence and moral activities among in-school adolescents in the state. The study adopted descriptive design. The sample for the study was one hundred and fifty (150) students in selected schools using simple random sampling technique. Two questionnaires were validated by experts. The reliability of the instruments was obtained through the test-retest method. The data collected were analyzed using PPMC and a reliability index of 0.73 was obtained. The data collected were analyzed using percentages to answer two research questions while null hypothesis was tested using Chi-square at 0.05 level of significance. The finding of the study revealed that the level of in-school adolescent on peer group influence is high. It was revealed from the finding of the study that the main types of moral actions displayed by in-school adolescent was social contract orientation. The study’s finding showed that there was no significant relationship between peer group influence and moral activities among in-school adolescents. Based on the findings, recommendations were made among others that teachers should pay more attention to students’ moral development in order to achieve the goals of senior secondary school.